2010
DOI: 10.1200/jco.2009.24.6314
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to Predict Subsequent Brain Metastasis in Patients With Metastatic Breast Cancer

Abstract: PURPOSE Brain metastasis is usually a fatal event in patients with stage IV breast cancer. We hypothesized that its occurrence can be predicted if a clinical nomogram can be developed, thus allowing for selection of enriched patient populations for prevention trials. PATIENTS AND METHODS Electronic medical records of patients with metastatic breast cancer were retrospectively reviewed for the period between January 2000 and February 2007 under a study approved by the institutional review board. A multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 32 publications
5
110
2
3
Order By: Relevance
“…Recorded cumulative incidence of BM was significantly higher for BC patients younger than 50 years (20.8%) compared to the older ones (9.7%) by observing follow-up during 5 years [11]. A series of independent studies which differed from each other by experimental design and patient subgroups involved, have, nevertheless, confirmed these main findings [12,13], namely:…”
Section: Brain Metastasis Risk Factors Associated With the Patient Agementioning
confidence: 88%
See 2 more Smart Citations
“…Recorded cumulative incidence of BM was significantly higher for BC patients younger than 50 years (20.8%) compared to the older ones (9.7%) by observing follow-up during 5 years [11]. A series of independent studies which differed from each other by experimental design and patient subgroups involved, have, nevertheless, confirmed these main findings [12,13], namely:…”
Section: Brain Metastasis Risk Factors Associated With the Patient Agementioning
confidence: 88%
“…Hence, premenopausal women sustainably demonstrate higher cumulative risks for BM development during the 5 years (3.8 vs. 2.8%), 10 years (6.2 vs. 4.2%), and 15 years (7.1 vs. 4.6%) of the follow-up observations performed after the initial BC has been diagnosed (P < 0.01) [9]. Indeed, more recent study performed with 2136 metastatic breast cancer patients has confirmed that in contrast to premenopausal women, the postmenopausal ones are at lower risk of BM development (HR = 0.68, 95% CI 0.54-0.86, P = 0.001) [12]. The significance of this risk impacted by the menopausal status (P = 0.008) has been further confirmed by an independent study [10].…”
Section: Menopausal Statusmentioning
confidence: 95%
See 1 more Smart Citation
“…Patients with lung metastasis also developed brain metastasis more frequently than those patients without lung metastasis [153,216,232]. Graesslin et al [233] developed a nomogram to predict brain metastasis in patients with metastatic breast cancer; significant predictors include younger age, higher histological grade, number of metastatic sites, short disease-free survival, and HER2 positivity.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Lin et al (16) reported that nearly 46% of women with metastatic TNBC developed brain metastasis that was associated with a median survival time of 4.9 months. Robust nomograms have also been developed that can help risk stratify women with metastatic breast cancer helping to identify groups most likely to develop brain metastases (18). However, with the relatively high overall incidence of brain metastases and the associated poor survival following its diagnosis among women with TNBC, a more practical and clinically meaningful research direction would be to identify groups of women with early stage TNBC who are at high risk of developing brain metastases.…”
Section: Introductionmentioning
confidence: 99%